2011
DOI: 10.1016/j.ygcen.2010.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Rapid increase in aggressive behavior precedes the decrease in brain aromatase activity during socially mediated sex change in Lythrypnus dalli

Abstract: In the bluebanded goby, Lythrypnus dalli, removal of the male from a social group results in a rapid behavioral response where one female becomes dominant and changes sex to male. In a previous study, within hours of male removal, aromatase activity in the brain (bAA) of dominant females was almost 50% lower than that of control females from a group in which the male had not been removed. For those females that displayed increased aggressive behavior after the male was removed, the larger the increase in aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 52 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…It is well established that sex change in many hermaphroditic fish is controlled by the social environment. Some studies have shown that changes in the social rank lead to a rapid and dramatic change of cortisol level and aggressive behavior in dominant females [Black et al, 2005[Black et al, , 2011Iwata et al, 2012]. Such alteration caused by the social situation might be closely related to the initiation of sex change.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that sex change in many hermaphroditic fish is controlled by the social environment. Some studies have shown that changes in the social rank lead to a rapid and dramatic change of cortisol level and aggressive behavior in dominant females [Black et al, 2005[Black et al, , 2011Iwata et al, 2012]. Such alteration caused by the social situation might be closely related to the initiation of sex change.…”
Section: Discussionmentioning
confidence: 99%
“…A number of neuromodulators have been investigated as a potential biological switch important for the initiation of sex change, including neural steroid hormones (i.e., estradiol, 11-ketotestosterone, testosterone, cortisol) (Godwin, 2010; Lorenzi et al, 2012), gonadotropin-releasing hormone, arginine vasotocin (Reavis and Grober, 1999; Godwin et al, 2000; Bass and Grober, 2001), aromatase (Black et al, 2011), and serotonin (Lorenzi et al, 2009), with an increasing interest in kisspeptin (Godwin, 2010). Despite this focus, the biological link between social environment and sex change has not been resolved.…”
Section: Sex Change In Teleost Fishesmentioning
confidence: 99%
“…In bluehead wrasse, although cyp19a1b expression clearly decreased with sex change, the trend was non-significant and only noticeable from stage 2, after behavioural changes first occur at stage 1. Likewise, Black, Balthazart [81] found whole brain aromatase activity declined only after behavioural changes in female-to-male sex change of the bluebanded goby (Lythrypnus dalli). Expression of cyp19a1b in bluehead wrasse fore/midbrain closely parallels gonadal cyp19a1a mRNA levels, and may reflect peripheral changes in E2 via putative oestrogen response elements in the cyp19a1b promotor [34].…”
Section: Aromatase and Isotocin In The Brainmentioning
confidence: 94%